Polydopamine Based Colloidal Materials: Synthesis and Applications. Issue 4 (10th November 2017) - Deng, Ziwei; Shang, Bin; Peng, Bo
Abstract: Polydopamine is a synthetic analogue of natural melanin (eumelanin) produced from oxidative polymerization of dopamine. Owing to its strong adhesion ability, versatile chemical reactivity, biocompatibility and biodegradation, polydopamine is commonly applied as a versatile linker to synthesize colloidal materials with diverse structures, unique physicochemical properties and tunable functions, which allow for a broad scope of applications including biomedicine, sensing, catalysis, environment and energy. In this personal account, we discuss first about the different synthetic approaches of polydopamine, as well as its polymerization mechanism, and then with a comprehensive overview of recent progress in the synthesis and applications of polydopamine‐based colloidal materials. Finally, we summarize this personal account with future perspectives. Abstract : Polydopamine based colloids are an important class of functional materials because they integrate bioinspired polydopamine chemistry from natural melanin and adhesive proteins secreted in mussel foots with colloidal science. We thereby review the recent progress in the synthesis and applications of polydopamine based colloidal materials.